Strategi Pemberdayaan Petani Berbasis Kearifan Lokal Muna: Pendekatan Sosial-Budaya dalam Penguatan Ketahanan Pangan - La Harudin; Nurmaya Nurmaya; Haerudin Tao (Journal of Humanities, Social Sciences, and Education, 2025)
Food security is one of the main pillars of sustainable development in Indonesia, particularly in rural areas that still rely on the agricultural sector as their primary source of livelihood. This study aims to examine farmer empowerment strategies based on the local wisdom of the Muna community using a socio-cultural approach as an effort to strengthen food security. Local wisdom of the Muna community, such as the kaghombo mutual cooperation system, rotating land management (kafo), and the karia harvest festival tradition, serve as social instruments that influence sustainable food production, distribution, and consumption patterns. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that local wisdom plays a significant role in building social solidarity, maintaining the sustainability of agricultural ecosystems, and minimizing the risk of crop failure. Effective empowerment strategies include strengthening customary-based farmer groups, training in agricultural technology aligned with local wisdom, and collaboration between traditional leaders, local government, and non-governmental organizations. The implications of this study indicate that integrating local values into farmer empowerment programs can improve food security while maintaining the cultural identity of the Muna community. Thus, a socio-cultural approach based on local wisdom is not only relevant to the local context of Muna but can also be replicated in other regions with similar social and cultural characteristics.